PERLINDUNGAN HUKUM TERHADAP PENUMPANG KERETA API ( KASUS KETERLAMBATAN KERETA API PERSFEKTIF FIQH SIYASAH) - Sriwindari, Henny; Khalid, Khalid (UNES Law Review, 2023)
When experiencing disruptions to train operations resulting in delays in arrival time, there are casualties and loss of property, PT. Kereta Api Indonesia (Persero) must be responsible for the impact of this incident, especially in terms of service to service users in accordance with Law Number 08 of 1999 concerning Consumer Protection. However, the delay experienced by train passengers is considered to still not meet the needs of passengers. In this study using normative juridical method. The formulation of the problem in this study is a) What is the accountability of PT. Kereta Api Indonesia (Persero) to passengers experiencing train delays? b) What is the legal protection for passengers who experience train delays based on Law Number 08 of 1999 concerning consumer protection.